The Effect of a Task-Based, Curriculum-Enrichment Program for Vocabulary Learning Strategies on Saudi University Students - Al-Yahya, Ibtesam Mohammed (International Journal of Linguistics, 2021)
The current study set to investigate the effect of introducing particular vocabulary learning strategies (VLSs) to Saudi, female students. The strategies implemented were six: ’grouping words together to study them’ (GW); ’putting English labels on physical objects’ (LO); ’using scales for gradable words’(SC); ’using semantic maps’(SM); ’using the keyword method’ (KW) and ’studying words with a pictorial representation of their meaning’ (PR). The participants were a group of 90 level-one students studying in the Department of English Language and Translation at Imam Muhammad Ibn Saud Islamic University, Riyadh. They were assigned to two groups: control (N= 44) and experimental (N=46); only the experimental group received instructions on those strategies in a form of task-based, curriculum-enrichment materials. To assess the effectiveness of such a VLS instruction (VLSI) program, three areas were examined: the students’ vocabulary learning (VL), the frequency of strategy-use, and their VLS repertoire. The data of the study were derived from three instruments: pre-post vocabulary achievement test (VAT), pre-post questionnaire and semi-structured interviews. The analysis of the data revealed the effectiveness of the VSBI program in the areas identified above. First, it improved the students’ vocabulary achievement as well as their VL, in general. Second, it increased the frequency of using general categories of VLSs (i.e. VLSs altogether, consolidation strategies, metacognitive strategies). It also increased the frequency of using five of the taught strategies which were GW, LO, SC, KW, and PR. Third, the VSBI program proved to be positive in that it changed and improved the students’ VLS repertoire.